EVALUASI PENERAPAN TAPPING BOX DALAM PENERIMAAN PAJAK.HIBURAN, PAJAK.RESTORAN, PAJAK.HOTEL, DAN.PAJAK PARKIR DENGAN.MENGGUNAKAN MODEL.END USER.COMPUTING SATISFACTION DI KOTA SUKABUMI - Rizky Fadhilah Nurjaman Kasahara; Rahma Nazila Muhammad (Faculty of Economics and Business, Universitas Warmadewa, 2023)
Tapping box is a hardware device to support online payment and reporting of local tax transactions listed in PERWALI Sukabumi City number 37 of 2018 and to support the tax collection system in Sukabumi City, namely the self-assessment system or paid for by the taxpayer himself. to find.out how the.application of.the tapping box, evaluate the application of the tapping box device and determine the impact of the application of the tapping box device on entertainment tax revenues, restaurant taxes, hotel taxes, and parking taxes in Sukabumi City. This type of research.uses qualitative.research methods.with a descriptive.approach. Data collection.techniques used.are interviews, observation, and.documentation, with an evaluation model using End User Computing Satisfaction (EUCS). The results.of the.research.conducted, (1) the tapping box device (hardware) has met the 8 mandatory characteristics of a system, until the first quarter of 2022 the tapping box device has been applied to as many as 42 devices for taxpayers in Sukabumi City. (2) The EUCS evaluation found that the software used to assist the tapping process provides completeness, convenience, and timeliness that has met the user's needs (brainware), only the accuracy of the resulting data does not reach 100%. (3) The impact of the application of tapping boxes is very influential in the receipt of entertainment taxes, restaurant taxes, hotel taxes, and parking taxes in Sukabumi City, but during the covid-19 pandemic the application of tapping boxes has no impact on increasing local taxes in Sukabumi City.